2014
DOI: 10.1039/c3qi00096f
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the copper–sulfur interaction in type 1 blue copper azurin by replacing Cys112 with nonproteinogenic homocysteine

Abstract: The Cu-SCys interaction is known to play a dominant role in defining the type 1 (T1) blue copper center with respect to both its electronic structure and electron transfer function. Despite this importance, its role has yet to be probed by mutagenesis studies without dramatic change of its T1 copper character. We herein report replacement of the conserved Cys112 in azurin with the nonproteinogenic amino acid homocysteine. Based on electronic absorption, electron paramagnetic resonance, and extended x-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Replacement of the Cys ligand in the Zn-binding site of the same protein to a His resulted in a green T1Cu site [64,65,67]. Both green and red T1Cu sites were engineered in the blue T1 site of azurin (Az) through incremental increase of strength to the axial Met by mutating it to a Cys or unnatural Hcy (homocysteine), respectively [68,69] (Figure 4b). …”
Section: Design Of Et Centersmentioning
confidence: 99%
“…Replacement of the Cys ligand in the Zn-binding site of the same protein to a His resulted in a green T1Cu site [64,65,67]. Both green and red T1Cu sites were engineered in the blue T1 site of azurin (Az) through incremental increase of strength to the axial Met by mutating it to a Cys or unnatural Hcy (homocysteine), respectively [68,69] (Figure 4b). …”
Section: Design Of Et Centersmentioning
confidence: 99%
“…This minimized energy status is known as the entatic or "rack-induced" state. 1,19,20 While the roles of primary coordination sphere (i.e., ligands that coordinate to the metal center directly) and secondary coordination sphere residues (i.e., residues that interact with the primary coordinating ligands) in tuning reduction potentials and reorganization energies of the T1 copper proteins have been extensively studied by site-directed mutagenesis and unnatural amino acids incorporation, [21][22][23][24][25][26][27][28][29][30] the impact of the changing the overall protein fold on the "rack-induced" state has not been explored. To address this issue, we report herein construction and characterization of circularly permutated variants of azurin, a T1Cu protein, and investigation of the effects of protein scaffold changes on both structural and functional properties of the T1Cu center.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Mononuclear cupredoxins have been studied for decades and almost all of them natively contain coordinately saturated Cu site and perform ET function. [1][2][3][4][5][6][7][8][9][10]13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The only exception so far is nitrosocyanin, which is in a cupredoxin scaffold but contains an additional water ligand. 31,32 Spectroscopic and x-ray crystallographic studies suggested that nitrosocyanin contains a type 2 copper (T2Cu) center, similar to many copper enzymes.…”
mentioning
confidence: 99%